Training Change Agents in CTA to Bring Health Care Transformation to Scale: The Case of Primary Care Practice Facilitators. (December 2016) - Potworowski, Georges; Green, Lee A.
Primary care medical practice is in a period of transformational change. Practices have limited capacity to cope with this transformation. Thousands of practices require support, and any intervention must both scale to that level and be usable by practices with limited change capacity. Various organizations train practice facilitators (PFs) to help with this transformation. We developed a training program for PFs to learn the basics of cognitive task analysis (CTA) to analyze and advise practices and to help them transform by improving macrocognitive functions. The training program comprised preparatory readings and 14 hr of didactic sessions and guided exercises over 2 days. That preparation was followed by a three-interview progression under actual field conditions: seconding for an experienced lead interviewer, leading with an experience interviewer as second, and leading with another PF as second. The data collection, analysis, and reporting are highly structured, tailored to the constraints of primary care, and scalable. Early experience with practices in Alberta indicates the resulting CTA reports to have significant impact. PFs have spontaneously transferred their use of CTA skills to other areas of their facilitation work.